Analisis Restrukturisasi Kredit Perbankan Untuk Meminimalisasi Kredit Bermasalah Saat Masa Pandemi Covid-19 - Betari Putri Pavita; Imam Mukhlis (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Non-performing loans remain one of the main challenges in maintaining the quality of banking credit disbursements, and credit restructuring policies are an option for banks to reduce their problem loans. This study aims to determine the application of credit restructuring from the Financial Services Authority Regulation Number 11 / POJK.03/2020 on National Economic Stimulus as a Countercyclical policy on the impact of the spread of Coronavirus Disease 2019 at PT Bank Jatim Malang Branch during the Covid-19 pandemic. The method used in this study is a qualitative method with a case study through interviews with resource persons. This study shows that credit restructuring can reduce the number of non-performing loans for Bank Jatim with a pattern of extension, delay, reduction of principal and interest installments, and the addition of credit facilities and a combination of these various patterns. Inhibitory factors are in the form of restrictions on appointments with debtors due to restrictions on public space by the government and the fault of the internal parties of the bank in analyzing the debtor's business that will make losses to the bank. While the supporting factor is this policy is a helpful program to succeed in the distribution of credit from the government by extending the period of realization of credit restructuring during the pandemic due to a decrease in the NPL number in 2020, it will be fully supported and developed by the government.